The therapeutic potential of hematopoietic stem cells in bone regeneration - Oliveira, Claudia S. (2022)
The repair process of bone fractures is a complex biological mechanism requiring the recruitment and in situ functionality of stem/stromal cells from the bone marrow (BM). BM mesenchymal stem/stromal cells have been widely explored in multiple bone tissue engineering applications, whereas the use of hematopoietic stem cells (HSCs) has been poorly investigated in this context. A reasonable explanation is the fact that the role of HSCs and their combined effect with other elements of the hematopoietic niches in the bone-healing process is still elusive. Therefore, in this review we intend to highlight the influence of HSCs in the bone repair process, mainly through the promotion of osteogenesis and angiogenesis at the bone injury site. For that, we briefly describe the main biological characteristics of HSCs, as well as their hematopoietic niches, while reviewing the biomimetic engineered BM niche models. Moreover, we also highlighted the role of HSCs in translational in vivo transplantation or implantation as promoters of bone tissue repair. Impact statement The ability of bone to natural self-heal depends on the size and stabilization level of the tissue fracture, and it is impaired in several pathophysiological conditions. Considering that the available treatment options have demonstrated limited regenerative performance, the hematopoietic stem cells (HSCs) co-cultured in different tissue engineering strategies have emerged as a powerful tool to promote effective bone regeneration and healing. Here, we reviewed the most important biomimetic bone-marrow hematopoietic niches and showed the regenerative potential of these cells, both in vitro and in translational in vivo transplantation/implantation approaches. This knowledge encourages the development of new HSC-related bone regenerative therapies.